Show off the efficiency of dai-liao method in merging technology for monotonous non-linear problems - Rana Z. Al-Kawaz; Abbas Y. Al-Bayati (Institute of Advanced Engineering and Science, 2021)
In this article, we give a new modification for the Dai-Liao method to solve monotonous nonlinear problems. In our modification, we relied on two important procedures, one of them was the projection method and the second was the method of damping the quasi-Newton condition. The new approach of derivation yields two new parameters for the conjugated gradient direction which, through some conditions, we have demonstrated the sufficient descent property for them. Under some necessary conditions, the new approach achieved global convergence property. Numerical results show how efficient the new approach is when compared with basic similar classic methods.